Can Academic Corruption Be Eradicated? - Reisberg, Liz (International Higher Education, 2021)
Corruption is pervasive in higher education worldwide, the result of a confluence of circumstances that make it attractive due to potential rewards and limited consequences. Many higher education systems unintentionally support perverse incentives for the proliferation of corruption. This article cites examples of corruption highlighted in a recently published volume, Corruption in Higher Education – Global Challenges and Responses.